Consonant aspiration in Mandarin-speaking children: a developmental perspective from perception and production - Li, Yani; Li, Qun; Du, Yihang; Wang, Lili; Li, Lin; Wen, Jian; Zheng, Yun (Frontiers in Pediatrics, 2025)
IntroductionThis study investigates Mandarin-speaking children's acquisition of aspirated/unaspirated voiceless consonants in terms of perception and production, to track children's developmental profile and explore the factors that may affect their acquisition, as well as the possible association between perception and production.MethodsMandarin-speaking children (N = 95) aged 3–5 and adults (N = 20) participated in (1) a perception test designed based on the minimal pairs of unaspirated/aspirated consonants in the quiet and noisy conditions respectively; (2) a production test where participants produced the target words, with syllable-initial consonants focusing on aspiration and non-aspiration. Six pairs of unaspirated/aspirated consonants in Mandarin were included.Results(1) Children's perception and production accuracy of aspirated and unaspirated consonants increased with age. Five-year-olds achieved high accuracy in the perception under the quiet condition and in the production (over 90%), though not yet adult-like. (2) Noise adversely affected children's perception, with all child groups showing poor performance in the noisy condition. In terms of perception, stops were more challenging to children than affricates, but in terms of production, children performed better on stops. Furthermore, the presence of noise had a greater detrimental effect on the perception of aspirated consonants compared to unaspirated ones. (3) A weak positive correlation was found between children's perception of consonant aspiration in the quiet condition and their production.DiscussionThe findings indicate that age, aspiration state, and manner of articulation (MOA) would affect children's acquisition of consonant aspiration. Although 5-year-olds have almost acquired aspirated/unaspirated consonants, compared to adults, the perception of consonant aspiration in noise remains a challenge for children.